A REMS Scan-Based Report on Relation Between Body Mass Index and Osteoporosis in Urban Population of Medan at Royal Prima Hospital (Majalah Kedokteran Bandung, 2020)
Body Mass Index (BMI) and osteoporosis are two major medical issues in practical life. Body Mass Index is recognized as an index to determine body fat mass while osteoporosis is a condition that decreases bone mass density and disrupts bone architecture, which will eventually affect bone strength and increase the risk of fracture. This study aimed to determine the relationship between BMI and osteoporosis using REMS. This was a cross-sectional study on 300 patients, 21 years of age and above, who underwent Radiofrequency Echographic Multi-Spectrometry (REMS) scan during October 2018 to September 2019 in Royal Prima Hospital, Medan, North Sumatra, Indonesia. Osteoporosis was defined based on densitometer parameters for spine and neck of femur while the BMI categories used were underweight (< 18.5 kg/m2), normal-weight (18.5-22.9 kg/m2), overweight (23-24.9 kg/m2), pre-obese (25-29.9 kg/m2), obese type 1 (BMI 30-40 kg/m2), and obese type 2 (40.1-50 kg/m2). Correlation between osteoporosis and BMI was analyzed using Spearman correlation test. The median BMIs for Spine osteoporosis and Neck of Femur osteoporosis groups were 23.24 and 22.51, respectively. Meanwhile, the central tendency of the bone mass density (gr/cm2) of the spine and neck of femur osteoporosis were 0.70 and 0.53, respectively. There was a significant correlation between BMI and the incidence of the neck of femur (R coefficient = -0.690) and spine (R = -0.390) osteoporosis. Hence, lower BMI increases the potential of the neck of femur and spine osteoporosis.Laporan Berbasis Pemindaian REMS tentang Hubungan Antara Indeks Massa Tubuh dan Osteoporosis pada Penduduk Kota Medan di Rumah Sakit Royal PrimaIndeks Massa Tubuh (IMT) dan osteoporosis merupakan dua masalah medis utama dalam kehidupan sehari-hari. Indeks Massa Tubuh telah diakui sebagai indeks yang digunakan untuk menentukan massa lemak tubuh sementara osteoporosis merupakan kondisi yang menurunkan kepadatan tulang dan mengganggu arsitektur tulang yang pada akhirnya memengaruhi kekuatan tulang dan meningkatkan risiko fraktur. Penelitian ini bertujuan untuk menentukan hubungan antara BI dan osteoporosis dengan menggunakan Radiofrequency Echographic Multi-Spectrometry (REMS). Penelitian ini merupakan penelitian potong lintang pada 300 pasien berusia 21 tahun ke atas yang menjalani pemindaian REMS selama periode Oktober 2018 sampai September 2019 di RS Royal Prima Medan. Osteoporosis ditentukan berdasarkan parameteri densitometri untuk tulang belakang dan leher femur sementara kategori BMI yang digunakan adalah berat badan (BB) kurang (
Keywords: Body Mass Index (BMI); Osteoporosis; Radiofrequency Echographic Multi-Spectrometry (REMS)